2016
DOI: 10.1021/acsami.6b07049
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Construction and Characterization of Chlorin-Based Supramolecular Aggregates in Tumor Cells

Abstract: We demonstrate in situ construction and characterization of supramolecular aggregates from chlorin p6 (Cp6) molecules in tumor cells. Fully deprotonated Cp6 molecules in neutral condition were partially protonated inside the acidic lysosomes of cells and significantly increased the hydrophobicity of them that resulted in simultaneous formation of J-type aggregates. Importantly, the formation of J-aggregates was fully characterized in artificial tissues by UV-vis, circular dichroism (CD) and transmission electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Cancer, broadly speaking represents another area where monitoring pH via PAI could be beneficial in the context of diagnostic and therapeutic applications. 8,36 It is well-known that the extracellular tumor microenvironment is slightly acidic, pH = 6.4–7.0. 37 Most cancer environments are also highly reducing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer, broadly speaking represents another area where monitoring pH via PAI could be beneficial in the context of diagnostic and therapeutic applications. 8,36 It is well-known that the extracellular tumor microenvironment is slightly acidic, pH = 6.4–7.0. 37 Most cancer environments are also highly reducing.…”
Section: Resultsmentioning
confidence: 99%
“…low pH, enzymes, and hydrogen peroxide (H 2 O 2 )). [7][8][9][10] However, most tetrapyrrolic PA systems are limited to the NIR region. 7,11 Absorption greater than 1000 nm, termed the second near-infrared region (NIR-II: 1000-1350 nm), allows for deeper tissue penetration and reduced light scattering than the NIR-I region (700−950 nm).…”
Section: Introductionmentioning
confidence: 99%
“…PA signals of RDNP conjugates have the positive correlation with molar extinction coefficient presented in UV–vis spectra (Figure S5). , According to the lowest and highest PA intensity ratio, the suitable wavelengths for analyzing aggregation were 710 and 750 nm, which could be more rational to monitor the aggregation index (Figure D). The I 750 / I 710 values of PA signals for P1 and P2 were 0.34 and 0.41, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Unlike from the others families of hybrid carbon nanomaterials [9], the potential applications in biological/pharmaceutical field of carbon based nanomaterials-porphyrins appear still scarcely investigated, especially for J-aggregates self-assemblies as well as their intracellular trafficking, therapeutic and imaging properties. In the literature, it was observed that hybrids nanomaterials based on porphyrinoids [24,63] were prepared at pH different from physiological conditions, and then treated with cells. In this context, future work will be devoted to studying the biocompatibility and cellular uptake of our hybrid MWCNTs/J-aggregates supramolecular systems.…”
Section: Discussionmentioning
confidence: 99%